Leisure-related mobility of elderly people: ways to sustainability - Stefanie Foebker; Reinhold Grotz (European Regional Science Association (ERSA), 2003)
Owing to grown life expectancy as well as increasing financial scope, car ownership and possession of driving licences, the elderly of today have numerous opportunities regarding their leisure activities. Serious health problems and social constraints are generally infrequent before the age of about 80. Thus, the first 10-20 years of retirement are characterized by good health and the absence of occupational and/or family commitments, allowing for an active leisure life. Leisure-related mobility among the elderly relies increasingly on private vehicles. Car use is the basis for a wider activity space, including locations that are far away and/or badly accessible by means of public transport. The resulting increase in motorized leisure-related traffic has negative ecological impacts. Thus, the question arises of how the elder population's leisure mobility can take place in a more sustainable manner. Within the FRAME project, 4,500 people aged 60+ were interviewed regarding their leisure activities. The empirical results give detailed information about determinants of and motives for leisure-related mobility. While leisure activities are largely determined by individual factors like health or car availability, other factors like settlement patterns and local leisure infrastructure also have significant influence. Therefore samples were taken from urban, suburban and rural areas. The FRAME household survey shows in how far elderly people from diverse sample areas differ with regard to their leisure activities, means of transport and distances travelled. To start with, the results show differences between sample groups from urban, suburban and rural areas. In addition, there are also variations within these three spatial categories. The paper intends to illustrate to what extent leisure-related mobility of the elderly is influenced by diverse spatial structures as well as the personal situation. We will discuss how individual residential settings affect leisure activities. Moreover, we will investigate the relation between infrastructure (local offers in leisure activities, transportation, etc.) and participation in local leisure activities and the selection of distant localities respectively. The results show, not surprisingly, large variations due to diverse equipments with leisure facilities. Interestingly, we also found substantial qualitative differences between urban, suburban and rural facilities resulting in distinct spatial orientation patterns. The results illustrating the relationship between spatial context and leisure-related traffic are used to evaluate which settlement structure is favourable to sustainable leisure mobility. We will identify local settings minimising leisure-related traffic and thus pollution. This aspect bears particular importance as the recreational wants of the growing number of elderly people have to be supplied. Attempting to mediate ecological and social demands, the paper aims to identify a set of conditions for the location and design of leisure facilities. These should promote sustainable mobility.
Keywords: 330